The press room - Purdy, Otto Independence (My University, 1899)
Introduction: The evolution that has taken place in the press within the last two centuries has been very great. Taking up the early history of the press we find that there is considerable evidence that the origin of printing has been traced back to ancient Assyrian nations, but the great progress which has taken place has been during modern times. In the early methods of printing we find that the people took their manuscript or whatever they desired to have printed, and wrote it out on a piece of very thin and transparent paper, pasted this on a block of hard wood, the engraver carved away, for a short distance, all that was not traced, after this was finished it was ready for impressions to be taken; the pressure was applied by means of a brush. No great progress was made along this line, the people evidently saw that it was a very slow and awkward method, and ceased to use it to any great extent. This earl form of printing is only in use by the Chinese to present. In Europe the same or a modified method lasted till the close of the fourteenth century.
Citation: Purdy, Otto Independence. The press room. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Early Printing; Evolution of the Press; Kinds of Presses; Cylinder Press; Theses; Manuscripts (documents)